Genetic dissection of two fibre yield-related stem traits in ramie (Boehmeria nivea L. Gaud). Issue 1 (1st January 2019) - Li, Fu; Zeng, Zheng; Yi, Langbo; Tang, Qingming; Peng, Qingzhong
Abstract: Ramie fibres are harvested from the stem bark of the plant, and thus two stem traits—the stem length (SL) and the stem diameter (SD)—are important components of fibre yield in this crop. A recently developed high-density genetic map using an F2 agamous line population derived from two parents, Qingdaye (QDY) and Zhongzhu 1 (ZZ1) laid the basis for dissection of the genetic basis of fibre yield-related traits. However, the genetic basis of the two fibre yield-related stem traits presented here is still uncharacterized in this population. In this study, quantitative trait locus (QTL) analysis for SL and SD traits was performed using the population of QDY/ZZ1, resulting in the identification of four SL and six SD QTLs. Among these 10 QTLs, one was detected in both environments, and six demonstrated a significant environmental correlation. Three DELLA genes were identified to cluster in the region of the stem length QTL qSL11b, and their encoding proteins displayed either amino acid-substitutions or amino acid-insertion/deletion in the functional GRAS domain between two parents. Because the DELLA protein is a negative regulator of the gibberellin signalling pathway and plays a central role in regulating the stem elongation, the mutations in the GRAS domain-encoding region of these three genes potentially influence stem growth. The identification of the QTLs for two stem traits will help improve the fibre yield in ramie breeding programmes by marker-assisted selection. The three identified DELLA genes are candidate genes for cloning the qSL11b locus in future studies.